Validación de la versión breve en español de la Escala UPPS-P de impulsividad para niños y adolescentes (BUPPS-P NA) - Caneto, Florencia; Pilatti, Angelina; Cupani, Marcos; Pautassi, Ricardo Marcos (Revista de Psicopatología y Psicología Clínica, 2020)
Validation of the Spanish version of the brief UPPS-P Impulsivity Scale for children and adolescents (BUPPS-P NA) Abstract: The Scale of Impulsivity for Children and Adolescents (UPPS-P NA) is a self-report instrument that assesses the impulsivity trait in children and adolescents. However, the UPPS-P NA does not have a short version in Spanish. The present study aimed to develop and validate a short Spanish version of the UPPS-P NA (BUPPS-P NA). First, the UPPS-P NA questionnaire was adapted to Spanish and validated in a sample of 257 children and adolescents (M age = 12.87, SD = 5.64; 61.9% female). Then, the BUPPS-P NA was developed and validated in a sample of 1777 children and adolescents (M age = 12.59, SD = 1.37; 54.2% women). The invariance of the BUPPS-P NA as to biological sex was evaluated also. The UPPS-P NA and BUPPS-P NA scales showed an adequate fit to the data. Also, the BUPPS-P NA Scale was invariant across sex. In summary, the BUPPS-P NA Scale presents adequate psychometric properties to measure the impulsivity trait in children and adolescents. Keywords: Trait impulsivity; childhood; adolescence; validity; reliability; invariance across sex. Resumen: La Escala de Impulsividad para Niños y Adolescentes (UPPS-P NA) es un instrumento de autoinforme que mide los rasgos de impulsividad en niños y adolescentes. Sin embargo, no posee una versión breve en español. El objetivo de este trabajo fue desarrollar y validar una versión breve (BUPPS-P NA) y en español de la UPPS-P NA. Para ello, primero se adaptó al español el cuestionario UPPS-P NA y se validó en una muestra de 257 niños y adolescentes (Medad = 12.87, DT = 5.64; 61.9% mujeres). Posteriormente, se desarrolló y validó el cuestionario BUPPS-P NA en una muestra de 1777 niños y adolescentes (Medad = 12.59, DT = 1.37; 54.2% mujeres). También se evaluó la invariancia del BUPPS-P NA en cuanto al sexo biológico. Los cuestionarios UPPS-P NA y BUPPS-P NA presentaron un ajuste adecuado a los datos. Asimismo, el cuestionario BUPPS-P NA resultó invariante en función del sexo. En resumen, la escala de impulsividad BUPPS-P NA presenta adecuadas propiedades psicométricas para medir impulsividad rasgo en niños y adolescentes. Palabras clave: impulsividad rasgo; niñez; adolescencia; validez; fiabilidad; invarianza en función del sexo.